The foreign direct investment in the commerce sector in Ecuador, period 2016 – 2022 - Ochoa Vásquez, Thais Alexandra (2024)
Foreign Direct Investment (FDI) is essential for the economy, especially in developing countries like Ecuador; To adapt to international demands, this country has implemented policies to attract FDI; However, it has not achieved effective channeling towards the commercial sector. For this reason, foreign direct investment in trade in Ecuador was analyzed from 2016 to 2022. We worked with a descriptive quantitative approach with documentary design and data from the Central Bank of Ecuador and the World Bank that were statistically analyzed. The results showed that FDI in Ecuador presents a varied trend because the trade sector fluctuates with moments of decline and rebound. It was concluded that despite the fluctuations in Ecuadorian trade during the period studied, FDI has played an important role in the country's economy and the importance of a legal framework that encourages foreign investments was highlighted.